2017
DOI: 10.1002/ird.2177
|View full text |Cite
|
Sign up to set email alerts
|

Drip Irrigation Scheduling Using Hydrus 2‐D Numerical Model Application for Strawberry Production in South‐West Spain

Abstract: Estimation of the optimum irrigation pulse duration and frequency is critical for any crop, and especially important in the typical sandy soil existing in the strawberry production area in south‐west Spain. Irrigation scheduling has been carried out using the numerical model Hydrus‐2D. The model has been calibrated with data from a soil tank experiment carried out in the laboratory. The optimum pulse duration has been estimated in three different crop stages, and has been compared with the irrigation schedulin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…In sandy soils, with a low water retention capacity, spatiotemporal hydraulic characterization is crucial [57,58]. As an example of watering difficulties in sandy soils, in a two-season study of irrigated potato cultivated in a sandy soil in USA, soil water storage and deep drainage at several zones across the farm were evaluated [57], detecting a significant spatiotemporal variability in soil water storage and temporal differences on deep drainage.…”
Section: • Weather Datamentioning
confidence: 99%
See 1 more Smart Citation
“…In sandy soils, with a low water retention capacity, spatiotemporal hydraulic characterization is crucial [57,58]. As an example of watering difficulties in sandy soils, in a two-season study of irrigated potato cultivated in a sandy soil in USA, soil water storage and deep drainage at several zones across the farm were evaluated [57], detecting a significant spatiotemporal variability in soil water storage and temporal differences on deep drainage.…”
Section: • Weather Datamentioning
confidence: 99%
“…As an example of watering difficulties in sandy soils, in a two-season study of irrigated potato cultivated in a sandy soil in USA, soil water storage and deep drainage at several zones across the farm were evaluated [57], detecting a significant spatiotemporal variability in soil water storage and temporal differences on deep drainage. To reduce deep drainage, soil water movement models like Hydrus 2-D were used to set the optimum duration of irrigation pulses in strawberries cultivated in extremely sandy soils in Spain, for each crop development stage [58].…”
Section: • Weather Datamentioning
confidence: 99%
“…Given the stability of the HYDRUS model, this software can be used to investigate the distribution of soil water and its movement under the surface and subsurface of drip irrigation systems [18][19][20][21]. It can also be used to design and evaluate the management of different irrigation systems, soils and crops [22][23][24]. To simulate an orchard, it is more interesting to use HYDRUS-3D than HYDRUS-2D because it simultaneously solves transport problems on all three axes and provides more realistic calculations of soil water distribution around the dripper.…”
Section: Introductionmentioning
confidence: 99%
“…In earlier studies, a good agreement between observed and simulated values for SWB components had been reported 7 , 23 , 24 . Previous research based evidences showed that under drip irrigation, Hydrus-2D was successfully calibrated and validated for SWB 25 , 26 , crop root water uptake 27 , 28 , soil wetting pattern 29 , 30 , irrigation scheduling 31 , 32 and to evaluate the nutrient transport and distribution pattern 33 , 34 . Aggarwal et al 23 compared the SWB in the scenario of CA and CT and found a very good agreement between observed and simulated values.…”
Section: Introductionmentioning
confidence: 99%